Enhancing assistant teachers' (PPM & PPM PPKI) psychological knowledge and skills in handling non-typically developed children in Sabak Bernam, Selangor - Ayub, Siti 'Ayunni; Abdul Khaiyom, Jamilah Hanum; Janon, Nazariah Shar'ie; Dollah, Abu Hassan (Knowledge Transfer Centre, Universiti Sains Malaysia, 2018)
The objective of this paper is to enhance psychological knowledge and skills of assistant teachers in managing and supervising non-typically developed children. The number of assistant teachers involved in this program is 50 participants ji-om 38 schools in Sabak Bernam. Assistant teachers in Malaysia are known as Pembantu Pengurusan Murid (PPM), and Pembantu Pengurusan Murid Program Pendidikan Khas Integrasi (PPM PPKI). Pre and post questionnaire are designed to assess assistant teacher's knowledge on non-typical . children based on 3 components which are knowledge, attitude and practice. Two modules are developed (Module 3 & Module 4) that consist of knowledge and skills required by assistant teachers to improve their understanding in handling non-typically developed children. The pre-test distributed during first meeting in Sabak Bernam, a month before the first workshop is conducted. Post-test is given at the end of every workshop. Result has shown an improvement of assistant teacher's knowledge and skills scores before and after the workshop. It is suggested the program reached its objectives and adequately improving PPM & PPM PPKI knowledge and skills in managing non-typical children.